IJTIHAD HAKIM DALAM MENYELESAIKAN SENGKETA EKONOMI SYARIAH DILINGKUNGAN PERADILAN AGAMA - Rusliani, Rusliani; Khulwah, Juhrotul (Ekonomi Islam, 2017)
This research discussed the settlement of sharia economic dispute in the environment of the religious court. The objective of the researchers analyzed the settlement of sharia economic dispute by litigation way in religious court. This research was the subject of thought to discuss the completion of dispute sharia economy in the religious court and analyze how a judge in taking legal decisions and using legal sources to be used as a reference in solving the dispute sharia economy. This research used descriptive analytic approach that was collecting and describing the results of subject matter then dissected by analyzing the object of research with primary and secondary data The results obtained were that the judges in resolving the dispute sharia economy using existing legal sources, both formal or material sources. but existing sources of law will not be able to run optimally without adequate legal competence. it is expected that the public should prioritize good behavior in conducting transactions in order to avoid the disputes that can arise in a transaction in order to create a safe and peaceful life.